Sex-specific effects of gastrointestinal microbiome disruptions on Helicobacter pylori-induced gastric carcinogenesis in INS-GAS mice - Chao Peng; Xin Li; Yu Li; Xinbo Xu; Yaobin Ouyang; Nianshuang Li; Nonghua Lu; Yin Zhu; Cong He (Biology of Sex Differences)
Abstract Background Accumulating evidence indicates that the dysbiosis of gastrointestinal microbiota is associated with the development of gastric carcinogenesis. However, the sex-specific traits of gastrointestinal microbiota and their correlation with the sexually dimorphic response to gastric cancer remain poorly understood. Methods Male and female transgenic FVB/N insulin-gastrin (INS-GAS) mice as a model of gastric cancer were randomly administered Brucella Broth or Helicobacter pylori (H. pylori). Stomachs were evaluated by histopathology. The gastric inflammation was examined by immunohistochemical and immunofluorescence staining. Gastric mucosal and fecal samples were collected for microbiota analysis using 16S rRNA gene sequencing. Results Following H. pylori infection, male mice showed heightened inflammatory infiltration and notably greater intestinal metaplasia compared to female mice. The structure of gastrointestinal microbiota was different between male and female mice, with relative higher diversity in females than males. Notably, we found gender disparities in the alterations of gastric and intestinal microbiota in mice post H. pylori infection. While the enrichment of Bifidobacterium and Lachnospiraceae was observed in female mice, Escherichia_Shigella and Akkermansia were more abundant in males. Furthermore, the microbial profile was distinct in estrogen-deficient ovariectomized (OVX) mice, including the overgrowth of Akkermansia and the loss of Butyricicoccus. Infected OVX females developed significantly more severe gastric lesions, which was normalized through co-housing with intact females. Conclusions We have identified a novel microbiome-based mechanism that provides insight into the sexual dimorphism in the development of H. pylori-associated gastric cancer.